Analisis Program Tanggung Jawab Sosial PT Bumi Konawe Mining - Tetiana Maksymchuk; Djuara Lubis; Ma’mun Sarma; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2017)
PT Bumi Konawe Mining (PT BKM) is a company with foreign (Russian) investment which is working in the field of excavating and trading nickel ore overseas. So far, the company owns only one nickel location, in Indonesia, which is on Wowonii island, South East Sulawesi. Company works through local consultant, because the owners are foreigners, which makes local community not to trust them. So the aim of this research is to reveal which level of the CSR mechanism fails to deliver proper result. The goals for the research are (1) To analyze the satisfaction of local community members by CSR program of PT. BKM; (2) To analyze the Corporate Image of PT BKM; (3) To maintain analysis of multi- cultural communication of PT. BKM and describe its mechanism on the basis of their carrying out the CSR program. The method used in this research is quantitative method with a questionnaire and supported by qualitative data obtained through direct interviews with data and respondents using the guide questions. The tool used for the quantitative section is SEM (structural equation modeling). Research using significance level 0.05 or 95% confidence level. The research results reflect that age significantly influence CSR Program, which means the younger the age, the bigger the satisfaction of the CSR Program. CSR program also significantly influence the Perception of the Company by local community members, if the value of a CSR program increases, so does the value of Perception of the Company by local community members, represented by the Image of the Company and Cross-Cultural Communication.